The Legal Liability of a Notary Who Conducts Unfair Competition by Notary Partners - Sukri, Sukri (Jurnal Konstatering, 2022)
Unfair competition between Notaries and colleagues, setting honorarium below the standard set by the Association is still common in Notary practice and this can trigger other Notaries to take similar actions in order to get as many clients as possible so that they get out of the corridor of the rule of law stipulated in the Law on Notary Positions and the Notary Code of Ethics. This study aims to determine the responsibility of a notary who commits unfair competition and the juridical implications of the actions of a notary who commits unfair competition. This research was conducted using a Juridical Sociological approach and an Explanatory Research specification. The data sources used are primary, secondary and tertiary data.Primary data collection was carried out using population techniques and sampling techniques. Data collection techniques using field research and library research. The data analysis method uses qualitative and descriptive data analysis. Research results show that: First, A notary who has committed unfair competition by not complying with the amount of honorarium determined by the association is a violation of the Notary's code of ethicsandcan be burdened with responsibility in the form of imposing ethical sanctions as determined and regulated in the regulations of the Indonesian Notary Association. Second, The juridical implications for a Notary who engages in unfair competition and withdraws honorarium below the minimum honorarium set by the Association, then the Notary can file a default lawsuit by the Association in this case by the Indonesian Notary Association by first giving a warning or subpoena to the Notary who has charge an honorarium below the minimum honorarium set by the Association.Keywords: Association; Honorarium; Responsibility.